CS-08 A CASE OF CD 57 NEGATIVE OLFACTORY GROOVE SCHWANNOMA IN WHICH SCHWANN / 2 E AND SOX10 WAS USEFUL FOR DISTINGUISHING FROM OEC TUMOR: A CASE REPORT AND REVIEW OF THE LITERATURES. (16th December 2019) - Masuda, Hiroyuki; Nemoto, Masaaki; Matsuzaki, Ryo; Matsura, Chie; Terazono, Sayaka; Mikai, Masataka; Ando, Shumpei; Harada, Masasi; Kondo, Kosuke; Harada, Naoyuki; Sugo, Nobuo
Abstract: INTRODUCTION: In the case of the differentiate between olfactory groove schwannomas(OGS) and olfactory ensheathing cell (OEC) tumors, CD57 which is the marker which is specific for Schwann cell is useful. We experienced a case of OGS that was negative for CD57. CASE PRESENTATION: This case was a 13-year-old girl. Medical history: She visited the pediatric department with a chief complaint of headache. On the magnetic resonance image (MRI), a tumorous lesion was found in the anterior skull base and was referred to our department. No dysosmia, visual impairment, or cafe au lait spots were observed. Past history: As a medical history, she has developed acute lymphocytic leukemia at the age of 1 and has achieved complete remission after chemotherapy. At that time, radiation treatment to the head was not performed. Neuroradiological findings: The tumor was strongly enhanced heterogeneously in Gadolinium (Gd) enhanced MRI and the angiography showed hypovascular. Progress after hospitalization: The tumor was clearly demarcated from the surrounding brain surface and adhered strongly to the cribriform plate. Eventually, all tumors were removed and the patient was discharged on the 10th postoperative day. Five years have passed since the operation, and no recurrence of the tumor has been confirmed by MRI. Pathological findings: Antoni A and Antoni B were seen by Hematoxylin & Eosin (H & E) staining. Immunostaining showed S-100 strong positive, Schwann / 2E and Sox10 positive, and CD57 negative. Discussion: In our case, CD57 (Leu7) was negative, but Schwann / 2E and Sox10 were positive, so OGS was diagnosed. CONCLUSION: We experienced a case of OGS that was negative for CD57 (Leu7) but positive for Schwann / 2E and Sox10. For pathological differentiation between OGS and the OEC tumor, Schwann / 2E and Sox10 immunostaining would also be necessary in addition to H & E stain and CD57 (Leu7).